Spiritual Well-Being and Mental Health During the COVID-19 Pandemic in Italy - Coppola, Ilaria; Rania, Nadia; Parisi, Rosa; Lagomarsino, Francesca (Frontiers in Psychiatry, 2021)
During the COVID-19 pandemic in Italy, people and families experienced a new and sudden situation that forced them to stay in their homes for a long period (February 25- May 26). In this context, many people found themselves in great difficulty, not only because of the fear of contagion or the economic problems deriving from the closure of production activities but also because the virus profoundly changed the way of life in society. The “Social distancing” concept became central in all personal relationships, including close family relationships. In this situation, our paper seeks to understand the role of spirituality and religiosity in reacting to this difficult situation and in particular on the physical and psychological health of the people involved. The data we present here are part of a multidisciplinary research with a quantitative theoretical framework. As the data was collected during the first Italian lockdown, a total of 1,250 adults from all over Italy participated in the on-line questionnaire. Among the main results it emerged that the participants perceived lower levels of spiritual well-being and mental health than the pre-pandemic situation with a significant gender difference; in fact, women perceived lower mental health than men. At the same time, it is evident that spirituality and religious practices are a protective factor connected not only with psychological and mental but also physical health. Finally, it appears evident that the family is a protective factor with respect to mental health, even in a period so full of stress factors, those who did not live alone and especially those who had to take care of small children reported higher perceived mental health and a greater ability to activate coping resources.